2015
DOI: 10.1590/0001-3765201520140286
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the effects of guava (Psidium guajava L.) infusions on germination, root tips and meristematic cells of Latuca sativa

Abstract: Guava (Psidium guajava L.) is a plant often employed in popular medicine. Recently several studies have alerted about the toxicity of substances present in medicinal plants, which can pose risks to the human health. In this sense, the present work aimed to investigate the phytotoxic, cytotoxic and genotoxic action of three guava varieties -Paluma, Pedro Sato and Roxa ("purple") -on the plant test system Lactuca sativa L. Thus, macro-and microscopic evaluations were carried out for five infusion concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Leucoanthocyans were only found from guava extracts. All the components checked in this study were reported in A. hispidum (Harekrishna et al, 2010), P. guajava (Barbalho et al, 2012;Luber et al, 2015) and S. alata (Onyegeme-Okerenta et al, 2017) preparations. In our scrutiny of literature, we did not find data from phytochemical profile of V. tonoreana.…”
Section: Qualitative and Quantitative Chemical Content Of Plant Extractsmentioning
confidence: 98%
See 1 more Smart Citation
“…Leucoanthocyans were only found from guava extracts. All the components checked in this study were reported in A. hispidum (Harekrishna et al, 2010), P. guajava (Barbalho et al, 2012;Luber et al, 2015) and S. alata (Onyegeme-Okerenta et al, 2017) preparations. In our scrutiny of literature, we did not find data from phytochemical profile of V. tonoreana.…”
Section: Qualitative and Quantitative Chemical Content Of Plant Extractsmentioning
confidence: 98%
“…Therefore, P. guajava spp. stand out in a list of 71 medicinal plant of interest according to the Brazilian Unified Health System (Luber et al, 2015). A scrutiny of the literature revealed the following components from known anti-filarial plant: β-sitosterol, kaempferol, glycoside and luteolin (Nateshan and Venkateswara, 2015), consequently identified from P. guajava (Metwally et al, 2011).…”
Section: Anti-filarial Activity Against Onchocerca Ochengimentioning
confidence: 99%
“…The comet assay was performed according to Singh et al [30]. Infusions (40 g L -1 ) of each studied guava cultivar, in aliquots of 25, 50, and 300 µL, were added to 300 µL of blood diluted in phosphate-buffered saline (PBS) at 50%.…”
Section: Comet Assay: Comet Assaymentioning
confidence: 99%